2022
DOI: 10.1002/jcsm.12924
|View full text |Cite
|
Sign up to set email alerts
|

Associations of device‐measured sleep, sedentariness and physical activity with growth differentiation factor 15 in older adults

Abstract: Background Growth differentiation factor 15 (GDF‐15) is a biomarker for chronic disease burden that might explain the health effects of sedentary behaviours (SBs) and physical activity (PA). We examined associations of device‐measured sleep, SB and PA, and time reallocations among them, with GDF‐15 in older adults. Methods We used data from 2245 older adults participating in the Seniors‐ENRICA‐2 study. Wrist‐worn accelerometers were employed to ascertain total time in sleep, SB, light PA (LPA) and moderate‐to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
2
0
4
Order By: Relevance
“…GDF-15, a member of TGF-b superfamily, has been identified as a marker of aging, muscle weakness, and frailty (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Several studies have demonstrated the link between GDF-15 and bone metabolism (19-21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GDF-15, a member of TGF-b superfamily, has been identified as a marker of aging, muscle weakness, and frailty (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Several studies have demonstrated the link between GDF-15 and bone metabolism (19-21).…”
Section: Discussionmentioning
confidence: 99%
“…Growth differentiation factor-15 (GDF-15), a member of the transforming growth factor b (TGF-b) superfamily, has been implicated as a biomarker of aging, sarcopenia, muscle wasting, cachexia, mitochondrial disease, decreased physical activity, and energy imbalance (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). As a circulating myokine, the serum level of GDF-15 is increased as a result of a metabolic response to muscle-specific mitochondrial stress and muscle dysfunction in humans (9,16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Com base nos estudos analisados, verificou-se que os despendem um tempo maior em comportamento sedentário, menor tempo de prática regular de atividade física, e apresentam alteração no tempo e qualidade do sono. Esses achados corroboram com outros estudos (Cabanas-Sánchez et al, 2019Dash et al, 2019;Gordon et al, 2019;Hu et al, 2020;Koolhaas et al, 2017;Ortolá et al, 2022;Seguin et al, 2014;Štefan et al, 2019;Wang et al, 2022) que, também, mostraram maior exposição ao CS, três desses comportamentos de movimento de 24hs, menores níveis de AF e alteração na quantidade e qualidade do sono. Apesar de poucos estudos, nessa RS as evidências indicam um aumento preocupante no CS, redução dos níveis de AF e alteração no sono entre os idosos.…”
Section: Discussionunclassified
“…Em geral, o ponto de corte utilizado para os idosos classificados como fisicamente ativos foi ≥ 150 min/semana. Por outro lado, todos os estudos que abordaram os três comportamentos de 24 horas (Gordon et al, 2019;Hu et al, 2020;Koolhaas et al, 2017;Ortolá et al, 2022;Reis et al, 2018;Štefan et al, 2019;Wang et al, 2022), apresentaram relação com maior exposição ao CS, e um ponto de corte ≥ 4h/dia. Quanto ao sono de boa qualidade, os pontos de corte variaram entre >7h/dia e <9h/dia (He et al, 2021;Smagula et al, 2016;Vancampfort et al, 2018;Zhang et al, 2017).…”
Section: Descrição Dos Estudosunclassified
See 1 more Smart Citation